2007
DOI: 10.1007/s00415-006-0313-x
|View full text |Cite
|
Sign up to set email alerts
|

Low awareness of transient ischemic attacks and risk factors of stroke in a Swiss urban community

Abstract: The study brings to light relevant deficits of stroke knowledge in our population. A small number of participants could recognize TIA as stroke related symptoms resolving completely within 24 hours. Only a third of the surveyed persons would seek immediate medical help in case of TIA. The information obtained will be used in the development of future educational campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 23 publications
9
53
2
Order By: Relevance
“…However, less than one third of the general public can come up with more than two symptoms or risk factors and even fewer are considered to have an adequate knowledge of stroke or TIA. Similar results have been reported throughout the United States and across Europe and Asia (Kothari et al 1997, Pancioli et al 1998, Yoon et al 2001, Reeves et al 2002, Greenlund et al 2003, Parahoo et al 2003, Centers for Disease Control and Prevention 2004, Ferris et al 2005, Müller-Nordhorn et al 2006, Nedeltchev et al 2007, Evci et al 2007, Mikulík et al 2008. Women have been found to have a better overall symptom awareness and knowledge of risk factors than men (Ferris et al 2005).…”
Section: Knowledge Of Stroke Among the Publicsupporting
confidence: 75%
“…However, less than one third of the general public can come up with more than two symptoms or risk factors and even fewer are considered to have an adequate knowledge of stroke or TIA. Similar results have been reported throughout the United States and across Europe and Asia (Kothari et al 1997, Pancioli et al 1998, Yoon et al 2001, Reeves et al 2002, Greenlund et al 2003, Parahoo et al 2003, Centers for Disease Control and Prevention 2004, Ferris et al 2005, Müller-Nordhorn et al 2006, Nedeltchev et al 2007, Evci et al 2007, Mikulík et al 2008. Women have been found to have a better overall symptom awareness and knowledge of risk factors than men (Ferris et al 2005).…”
Section: Knowledge Of Stroke Among the Publicsupporting
confidence: 75%
“…15 Although previous studies have suggested that women, 6,8,10,12,13 and either young 10,13,16 or middle aged 12,14 patients have better knowledge and awareness of TIA and stroke the present study showed no sex or age-related differences in the responses obtained. Other reports have also highlighted that awareness of cerebrovascular disease is better in those with higher levels of education 6,8,[10][11][12]14,16,17 and higher income. 8,16,17 In this study 65% of respondents were socioeconomic class I and II and would be expected to be more knowledgeable suggesting that for the wider population appropriate responses to TIA are even less likely.…”
Section: Discussioncontrasting
confidence: 63%
“…Although the study cohort appeared uninformed about cerebrovascular disease, this data would seem to mirror those of the Swiss study in which 87.2% of people did not recall having heard the term 'transient ischaemic attack' and only 2.8% regarded TIA as a potentially harmful event, 6 even though their subsequent responses were more likely to be appropriate. In contrast, this lack of public awareness that TIA is a medical emergency was also evident in another recent study where only 44.4% of patients sought medical attention following a TIA.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Authors from Switzerland and the US demonstrated only 8.3% 13 and 8.6% 14 of the public sampled understood the symptoms of TIA. In addition, only 2.8% of the public appreciated the need for urgent medical attention following TIA.…”
Section: Discussionmentioning
confidence: 98%